Biodegradable Magnesium Biomaterials—Road to the Clinic - Shukufe Amukarimi; Masoud Mozafari (Bioengineering, 2022)
In recent decades, we have witnessed radical changes in the use of permanent biomaterials. The intrinsic ability of magnesium (Mg) and its alloys to degrade without releasing toxic degradation products has led to a vast range of applications in the biomedical field, including cardiovascular stents, musculoskeletal, and orthopedic applications. With the use of biodegradable Mg biomaterials, patients would not suffer second surgery and surgical pain anymore. Be that as it may, the main drawbacks of these biomaterials are the high corrosion rate and unexpected degradation in physiological environments. Since biodegradable Mg-based implants are expected to show controllable degradation and match the requirements of specific applications, various techniques, such as designing a magnesium alloy and modifying the surface characteristics, are employed to tailor the degradation rate. In this paper, some fundamentals and particular aspects of magnesium degradation in physiological environments are summarized, and approaches to control the degradation behavior of Mg-based biomaterials are presented.